Effects of azacitidine in 93 patients with IDH1/2 mutated acute myeloid leukemia/myelodysplastic syndromes: a French retrospective multicenter study. Issue 2 (28th January 2021) - Willekens, C.; Rahme, R.; Duchmann, M.; Vidal, V.; Saada, V.; Broutin, S.; Delahousse, J.; Renneville, A.; Marceau, A.; Clappier, E.; Uzunov, M.; Rossignol, J.; et al.
Abstract: Isocitrate dehydrogenase 1 ( IDH1 ) and 2 ( IDH2 ) mutations in Myeloid Neoplams (MNs) exhibit DNA hypermethylation via 2-hydroxyglutarate (2HG) over-production. Clinical impact of azacitidine (AZA) remains inconsistent in IDH1/2 -mutated MNs and the potential of serum 2HG as a suitable marker of response to AZA is unknown. To address these questions, we retrospectively analyzed 93 MNs patients (78 AML, 11 MDS, 4 CMML) with IDH1 / 2 mutations treated with AZA. After a median of 5 cycles of AZA, overall response rate was 28% (including 15% complete remission) and median OS was 12.3 months (significantly shorter in AML compared to MDS/CMML patients). In multivariate analysis of AML patients, DNMT3A mutation was associated with shorter OS while IDH1/2 mutation subtypes had no independent impact. No difference was observed in serum 2HG levels upon AZA treatment between responding and refractory patients suggesting that serum 2HG cannot be used as a surrogate marker of AZA response.